Optimization of peptide-based polyagonists for treatment of diabetes and obesity. Issue 10 (1st June 2018) - Knerr, Patrick J.; Finan, Brian; Gelfanov, Vasily; Perez-Tilve, Diego; Tschöp, Matthias H.; DiMarchi, Richard D.
Graphical abstract: